2014
DOI: 10.3390/agronomy4030418
|View full text |Cite
|
Sign up to set email alerts
|

Field Phenotyping of Soybean Roots for Drought Stress Tolerance

Abstract: Root architecture was determined together with shoot parameters under well watered and drought conditions in the field in three soybean cultivars (A5409RG, Jackson and Prima 2000). Morphology parameters were used to classify the cultivars into different root phenotypes that could be important in conferring drought tolerance traits. A5409RG is a drought-sensitive cultivar with a shallow root phenotype and a root angle of <40°. In contrast, Jackson is a drought-escaping cultivar. It has a deep rooting phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(192 citation statements)
references
References 38 publications
7
174
1
10
Order By: Relevance
“…Largely, roots are the first organ to perceive and respond to DS, before other plant organs, and communicate this information to the shoot (Konings and Jackson 1979;Bano et al 1993;Ritchie 1981;Sauter et al 2001;Chaves et al 2003;Trachsel et al 2010;Fenta et al 2014). Numerous other studies have shown that plant roots can sense changes in abiotic factors such as water content Wilkinson and Davies 2002), oxygen content (Drew et al 1990) and the nutrient composition (Schachtman and Shin 2007) of the soil.…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…Largely, roots are the first organ to perceive and respond to DS, before other plant organs, and communicate this information to the shoot (Konings and Jackson 1979;Bano et al 1993;Ritchie 1981;Sauter et al 2001;Chaves et al 2003;Trachsel et al 2010;Fenta et al 2014). Numerous other studies have shown that plant roots can sense changes in abiotic factors such as water content Wilkinson and Davies 2002), oxygen content (Drew et al 1990) and the nutrient composition (Schachtman and Shin 2007) of the soil.…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 99%
“…Recent studies on the importance of size of roots to grain yields and the timing of soil water utilisation for maximising grain yields under terminal DS had drawn variable conclusions such as positive (Sponchiado et al 1989;White and Castillo 1992;Eghball and Maranville 1993;Kramer and Boyer 1995;Lynch 1995Lynch , 2013Pandey et al 2000aPandey et al , 2000bLiao et al 2004;Nord and Lynch 2009;Puangbut et al 2009;Lopes and Reynolds 2010;Manschadi et al 2010;Zhu et al 2010;Franco et al 2011;Kell 2011;Trachsel et al 2011;Suji et al 2012;Wasson et al 2012Wasson et al , 2014Comas et al 2013;Jaramillo et al 2013;Uga et al 2013; Root traits contribution to drought tolerance Functional Plant Biology Fenta et al 2014;Chimungu et al 2014aChimungu et al , 2014bLynch et al 2014;Bishopp and Lynch 2015) and negative or null (Ritchie 1981;Dardanelli et al 2004;CIAT 2007CIAT , 2008Beebe et al 2009;Itoh et al 2009;Ma et al 2010;Manavalan et al 2011;Ratnakumar et al 2009;Zaman-Allah et al 2011;Kumar et al 2012;…”
Section: Adaptation To Terminal Droughtmentioning
confidence: 99%
“…Many studies have highlighted that large LA is a valuable trait in breeding programs for improving yield [6,[13][14][15][16]. For example, genetic material from Indonesian tropical japonica rice landraces was used to create broader leaves in a breeding program for New Plant Type (NPT) to improve grain yields [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in rainfall were applied only to water amount, with no change in the number of wet days, which increased simulated runoff and deep drainage. If from one side it can be considered a limitation of this kind of analysis, from the other these results show the importance of improving the soil management, under such scenarios, to reduce runoff (FRANCHINI et al, 2009), such as no-tillage (BERTOL et al, 2008) and contour sowing and strip cropping (BORGES et al, 2014). DSSAT and MONICA were the models that presented the highest yield changes with rainfall variation, similar tendency observed in the analysis of the baseline (Figure 2), with these models being more sensitive to dry years than others.…”
Section: Rainfall Responsesmentioning
confidence: 99%
“…The air temperature also affects the photosynthesis rate, due to the balance between gross photosynthesis and maintenance respiration, defining the photoassimilates available to crop growth (PEREIRA et al, 2002). The most suitable range of temperature for soybean crop is between 20 and 30°C (FARIAS et al, 2009), although higher gross photosynthesis can be observed till 40°C . Extremes values also affect soybean, reducing development and growth.…”
Section: Introductionmentioning
confidence: 99%